CULTURAL DIVERSITY IN ENGLISH LANGUAGE LEARNING IN THAILAND AND LATVIA - Rudzinska, Ieva; Khampirat, Buratin (Journal of Education Culture and Society, 2019)
Aim. The article examines the characteristics of learning English in students from different cultural backgrounds – Thailand and Latvia. We aimed to gain empirical evidence of how the cultural background influences student leisure time English language learning habits and their English language learning anxiety. Concept and Methods. In the study two questionnaires were used: leisure time use of reading and writing activities in English (RWA), and English language learning anxiety scale (ELLAS). RWA included five areas of leisure time use of reading and writing activities:  using Internet or e-mail, writing regularly, reading regularly, watching TV or movies, and having checker; ELLAS consisted of four subscales - Communication Anxiety, Fear of Negative Evaluation, Test Anxiety, and English Classroom anxiety. The participants in the study were 95 undergraduate sports science program students from Thailand and Latvia – Thai students were 50, and 45 students represented Latvia. The research was carried out in two stages, first one being a pilot study.Results and Conclusions. The results showed that Thai and Latvian students showed more similarities in their leisure time use of reading and writing activities in English than differences: they often watched movies and TV, but rarely were reading and writing to improve their English. Latvian students spent more time watching TV, movies, reading regularly, using Internet or e-mail than Thai students (p < .01 and .05). Both Thai and Latvian students experienced moderately elevated communication anxiety, fear of negative evaluation, test anxiety, and English classroom anxiety. However, Thai students had higher anxiety than Latvian students in all aspects of ELLAS (independent samples t-test, statistically significant level of .01).